Prevalence and spatial distribution of sexually transmitted infections, HIV/AIDS and Hepatitis B and C in the city of Fernandópolis SP (Research, Society and Development, 2022)
Considering fundamental human rights, sexual and reproductive rights can be highlighted, and their respect promotes life in society, the study of infection control mechanisms caused by sexually transmitted infections (STI) is a topic of interest of different professionals involved in public health. The objective of this study was to identify the number of cases of HIV/AIDS and Viral Hepatitis (B and C) in the city of Fernandópolis in the years 2016 to 2020 and by georeferencing, to analyze their incidence and prevalence in the city of Fernandópolis. As a result, it was found that 21.43% of HIV positive pregnant women aged 15 to 25 years and 78.57% in pregnant women aged 26 to 45 years. HIV/AIDS notifications in the period from 2016 to 2020 were a total of 215 cases, which, 11.17% in the age group between 15 and 25 years and 29.77% in the age group between 38 and 48 years, having a moderate spatial correlation (r=0.621) among these age groups, with the highest involvement in the most populous neighborhoods. In the notifications of Viral Hepatitis (B and C) the lowest incidence was in the age group from 15 to 25 years old (2.45%) and the highest incidence in the age group from 55 to 70 years old (34.97%) with low spatial correlation between these age groups (r=0.427). The scientific evidence of this research will be able to subsidize the decision-making process, the formulation and the implementation of public policies of these diseases, within the program of confrontation for the STIs designated by the SUS.